1994
DOI: 10.1007/bf01499328
|View full text |Cite
|
Sign up to set email alerts
|

"Modern" death qualification: New data on its biasing effects.

Abstract: We report on the results of a comprehensive statewide survey of death penalty attitudes in which respondents were categorized in terms of their death-qualified or excludable status under several different Supreme Court doctrines governing the death-qualification process. We found that although changes in public opinion with respect to the death penalty in general have altered the relative sizes of the death-qualified and excludable groups, significant differences remain between them on a number of attitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 26 publications
2
52
1
Order By: Relevance
“…Previous research has found that jurors who are excluded from capital jury service because of their beliefs about the death penalty are more receptive to mitigating than aggravating circumstances (Butler & Moran, 2002;Luginbuhl & Middendorf, 1988;Robinson, 1993;Haney et al, 1994). However, the impact of other individual difference variables on jurors' evaluations of aggravating and mitigating circumstances in capital trials has yet to be empirically examined.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research has found that jurors who are excluded from capital jury service because of their beliefs about the death penalty are more receptive to mitigating than aggravating circumstances (Butler & Moran, 2002;Luginbuhl & Middendorf, 1988;Robinson, 1993;Haney et al, 1994). However, the impact of other individual difference variables on jurors' evaluations of aggravating and mitigating circumstances in capital trials has yet to be empirically examined.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, the focus of jurors' attention is drawn away from the presumption of innocence and onto post-conviction events. The time and energy spent by the court presents an implication of guilt and suggests to jurors that the penalty is pertinent, if not inevitable (Haney et al, 1994). Death qualification also forces jurors to imagine themselves in the penalty-phase proceeding.…”
Section: Introductionmentioning
confidence: 96%
“…Using Bayesian hierarchical models, Stasny, Kadane, and Fritsch (1998) reported support for the belief that jurors who would be excluded from death penalty juries behave differently from other jurors in non-capital offense trials. Surveys and experiments yield similar results (Cowan, Thompson, and Ellsworth 1984;Fitzgerald and Ellsworth 1984;Haney, Hurtado, and Vega 1994). Eisenberg and Wells (1992) used simple hypothesis tests to show that jurors' misperceptions about how long a murderer will actually serve in prison can lead them to impose the death penalty when they otherwise would not, a result partly relied on by the Supreme Court in Simmons v. South Carolina (1994).…”
Section: Deeper Understanding Of Capital Casesmentioning
confidence: 74%
“…Narby, 1992;Ellsworth, Bukaty, Cowan, & Thompson, 1984), and are more susceptible to the pretrial publicity that inevitably surrounds capital cases (Butler, 2007b). Finally, death-qualified jurors are more likely to believe in the infallibility of the criminal justice process and less likely to agree that even the worst criminals should be considered for mercy (Butler & Moran, 2002;Butler & Wasserman, 2006;Fitzgerald & Ellsworth, 1984;Haney, 1984aHaney, , 1984bHaney, Hurtado, & Vega, 1994;Moran & Comfort, 1986;Robinson, 1993;Thompson, Cowan, Ellsworth, & Harrington, 1984).…”
Section: Introductionmentioning
confidence: 95%